Niche opportunity created by land cover change is driving the European hare invasion in the Neotropics - Pasqualotto, Nielson; Boscolo, Danilo; Versiani, Natalia F.; Paolino, Roberta M.; Rodrigues, Thiago F.; Krepschi, Victor G. [UNESP]; Chiarello, Adriano G. (Springer Nature, 2020)
The European hare (Lepus europaeus) was introduced in the late 19th century in Argentina and has since rapidly expanded northwards, currently occupying the Brazilian south and southeast. Although European hare is known to be a farmland specialist in its native Europe, what habitat types or landscape features are facilitating its expansion in the Neotropics are not yet clear. Here we assessed support to the disturbance and biotic resistance hypotheses as general drivers of this invasion. We sampled with camera-traps and track surveys 205 sites in three landscapes in southeastern Brazil. We used occupancy models that corrected for both false positive and false negative errors. The disturbance hypothesis was the top-ranked (w = 0.66) with the amount of field, sugarcane, and managed forests all affecting strongly and positively hare occupancy. Support to the biotic resistance hypothesis was lower (ΔAICc = 2.14; w = 0.23) and partial, since only native forests showed a negative effect on hare occupancy. Our findings indicate that in the expansion front occupancy of this invader is mainly dictated by niche opportunities created by native habitat transformation into agricultural lands. The biotic resistance imposed by remaining native habitats seems to play a secondary role and only due to native forests. We conclude that hare geographical expansion should increase given the prominent role of Brazil as a commodity producer and exporter. Nevertheless, fomenting forested protected areas and improving adherence of rural owners to the Brazilian Forest Act, which protects forests in private rural properties, might help lessen this spread.
Keywords: Agricultural landscape; Human-disturbed habitats; Invasion biology; Lepus europaeus; Misidentification model; Occupancy